PERENCANAAN SISTEM KELISTRIKAN PADA ALAT X RAY MOBILE BERBASIS SOLARCELL DI RUMAH SAKIT HAJI MEDAN - Januari, Ihwal (Power Elektronik : Jurnal Orang Elektro, 2024)
The use of mobile X-ray equipment in hospitals is key in providing fast and efficient diagnostic services, especially in remote areas or in emergency situations. However, reliance on conventional energy resources is often a constraint in the mobility and availability of these services. This study aims to explore the potential of solar energy integration on mobile X-ray equipment as a solution to improve energy sustainability in hospitals. The use of solar power generation on mobile X-ray equipment has the potential to reduce dependence on conventional energy resources, reduce long-term operational costs, and provide wider access to healthcare services, especially in areas that are difficult to reach by the main power grid, this step will support the transformation towards a more sustainable and inclusive health system. This research provides a foundation for further development in the implementation of solar-based mobile X-ray equipment in hospitals and the health sector as a whole.